THE CHALLENGING DREAM OF PLANTS IN SPACE - Guadagno, Carmela Rosaria; Virzo De Santo, Amalia; D'Ambrosio, Nicola (Annales Kinesiologiae, 2015)
Plants are essential components of Bioregenerative Life Support Systems (BLSS) because they provide fresh food, produce oxygen, uptake CO2 from air and purify waste water via the leaf transpiration processes. In the consideration of long-duration human space missions, the issue of food production is becoming increasingly important. Therefore the possibility of growing plants in space represents the challenge for human space missions on the Moon and Mars and is related to the development of appropriate BLSS. Key issues include food production, nutritional needs, hydroponic techniques, horticultural requirements, waste processing and engineering systems.